Peran Manajemen SDM Dalam Meningkatkan Karir Karyawan Pada Dinas Koperasi dan UKM Provinsi Jawa Timur - Ricia Ratri Widodo; Menur Kusumaningtyas (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
The purpose of this study is to investigate how human resource management in East Java Province's Department of Cooperatives and Small and Medium Enterprises affects workers' professional advancement. Qualitative methods including documentation, interviews, and observations were used in the research. This research presents a significant challenge due to its qualitative nature and phenomenological approach. Human resource management's impact on workers' professional development in East Java Province's Department of Cooperatives and Small and Medium Enterprises is the subject of this phenomenological investigation. Indicators include scholarship information, fair career behaviour, and attention from direct superiors. A person's capacity to obtain a job or position that satisfies their life demands can be enhanced through career development. When people in a group or social setting act in a certain way, it can have a major effect on the outcome of the situation. This is called a role. Employees of the East Java Province Department of Cooperatives and Small and Medium Enterprises benefit from HR management in terms of career development, according to research. Each line and department is responsible for certain tasks in keeping with the existing organisational structure of the corporation. Consequently, employees are well-managed because they are given the resources they need to succeed in their future jobs and contribute to the company's success.